Novel gene function revealed by mouse mutagenesis screens for models of age-related disease - Potter, Paul K.; Bowl, Michael R.; Jeyarajan, Prashanthini; Wisby, Laura; Blease, Andrew; Goldsworthy, Michelle E.; Simon, Michelle M.; Greenaway, Simon; Michel, Vincent; Barnard, Alun; Aguilar, Carlos; Agnew, Thomas; et al. (Nature communications, 2016)
Determining the genetic bases of age-related disease remains a major challenge requiring a spectrum of approaches from human and clinical genetics to the utilization of model organism studies. Here we report a large-scale genetic screen in mice employing a phenotype-driven discovery platform to identify mutations resulting in age-related disease, both late-onset and progressive. We have utilized N -ethyl- N -nitrosourea mutagenesis to generate pedigrees of mutagenized mice that were subject to recurrent screens for mutant phenotypes as the mice aged. In total, we identify 105 distinct mutant lines from 157 pedigrees analysed, out of which 27 are late-onset phenotypes across a range of physiological systems. Using whole-genome sequencing we uncover the underlying genes for 44 of these mutant phenotypes, including 12 late-onset phenotypes. These genes reveal a number of novel pathways involved with age-related disease. We illustrate our findings by the recovery and characterization of a novel mouse model of age-related hearing loss. Random mutagenesis can uncover novel genes involved in phenotypic traits. Here the authors perform a large-scale phenotypic screen on over 100 mouse strains generated by ENU mutagenesis to identify mice with age-related diseases, which they attribute to specific mutations revealed by whole-genome sequencing.